REPRESENTASI KEGANASAN PADA IKLAN OREO DI TELEVISI (ANALISIS SEMIOTIKA ROLAND BARTHES MENGENAI MAKNA IKLAN OREO VERSI PENUH KEAJAIBAN DI TELEVISI) - Nick Diocto; Yasir " (Jurnal Online Mahasiswa (JOM) Bidang Ilmu Sosial dan Ilmu Politik, 2017)
Ads in this era of globalization and consumerism is currently regarded as the most effective medium of a series of activities to promote products that emphasize the imaging element. Ads that have been processed using the media leveled so that the mob can take it. Oreo is a snack food product or snacks are widely popular with the public from all walks of life, seen from the current segmentation Oreo not only focus on children, but to teenagers and adults as well. Oreo theme "miraculous" in its advertising this time and packed using visualization animation on his ads. There are two Oreo ad that uses animated version, it is the "Shark" and "Vampire" in the selection of advertising character is animal and ferocious mythical creatures and creepy. The study aims to find out "Representation Meaning of malignancy Contained in Oreo ads on television".The Method in this study is Qualitative using Semiotic Analysis of Roland Barthes, which is part of the method of data analysis in qualitative research as a representative. Presentation of the use of Roland Barthes Semiotics analysis to dissect the data collected through the study of literature and documentation. The data used are taken from the mass media, namely television and some other references from Youtube. Once the data was collected, the analysis of these methods will do to get results.These results indicate that visual ads oreo in the use of characters can be interpreted as the use of characters Sharks are predators of the ocean. And the figure of vicious described by Vampires will eat woman yellow-haired, but that has not happened yet turn out to be a good and friendly after the character eating a biscuit oreo, use of characters coming vicious aims to strengthen the miracle would happen if these characters would share or eat Oreo together with their prey. By Verbal use of a jingle is useful to strengthen the narrative of visualization in the ad, the content of the jingle that said it would be a character malignancy itself. In the representation, the use of the characters and the magic that happens is an aberration because the reality does not match the facts existing reality. And the use of Western ideology that popularized western culture through advertising.Keyword: Representasi Keganasan Pada Iklan, Analisis Semiotika Roland Barthes Pada Iklan Televisi